Knock-Down of GPR88 in the Dorsal Striatum Alters the Response of Medium Spiny Neurons to the Loss of Dopamine Input and L-3-4-Dyhydroxyphenylalanine - Ingallinesi, Manuela; Galet, Benjamin; Pegon, Jonathan; Faucon Biguet, Nicole; Do Thi, Anh; Millan, Mark J; Mannoury la Cour, Clotilde; Meloni, Rolando (Frontiers in Pharmacology, 2019)
The effects of L-3-4-dyhydroxyphenylalanine (L-DOPA) treatment for replacing the dopamine (DA) loss in Parkinson’s disease (PD) progressively wear off and are hindered by the development of dyskinesia, prompting the search for new treatments. The orphan G protein-coupled receptor 88 (Gpr88) represents a potential new target, as it is highly and almost exclusively expressed in the projecting gamma-Aminobutyric Acid-ergic (GABAergic) medium spiny neurons of the striatum, is implicated in motor activity, and is downregulated by 6-hydroxydopamine (6-OHDA) lesions, an effect that is reversed by L-DOPA. Thus, to evaluate Gpr88 as a potential target for the management of PD and L-DOPA–induced dyskinesia (LID), we inactivated Gpr88 by lentiviral-mediated knock-down with a specifically designed microRNA (miR) (KD-Gpr88) in a 6-OHDA rat model of hemiparkinsonism. Then, we investigated the effects of the KD-Gpr88 in the DA-deprived dorsal striatum on circling behavior and LID as well as on specific markers of striatal neuron activity. The KD-Gpr88 reduced the acute amphetamine-induced and increased L-DOPA–induced turning behavior. Moreover, it normalized the upregulated expression of striatal Gad67 and proenkephalin provoked by the 6-OHDA lesion. Finally, despite promoting ΔFosB accumulation, the KD-Gpr88 was associated neither with the upregulation of prodynorphin, which is causally linked to the severity of LID, nor with the aggravation of LID following chronic L-DOPA treatment in 6-OHDA–lesioned rats. These results thus justify further evaluation of Gpr88 as a potentially novel target for the management of PD as an alternative to L-DOPA therapy.